Successive Harvests Affect Yield, Quality and Metabolic Profile of Sweet Basil (Ocimum basilicum L.) - Giandomenico Corrado; Pasquale Chiaiese; Luigi Lucini; Begoña Miras-Moreno; Giuseppe Colla; Youssef Rouphael (Agronomy, 2020)
Sweet basil (Ocimum basilicum L.) is an aromatic, tender leafy green cultivated for the fresh market and industrial processing. Like many other leafy vegetables, this species can be harvested more than once to increase productivity. Although the cut-and-come-again (CC) harvest strategy is widespread in basil, not much is known about the effect of the cut. In this work, we examined differences in biomass, physiology, nutrient use efficiency and antioxidant capacity of basil leaves from two successive harvests. Moreover, we also performed an untargeted metabolomics analysis to reveal variations in the leaf metabolite profile. The data indicated that the cut affected many of the parameters under investigation, including a modest reduction of yield (−20%), of nitrogen use efficiency (−21%) and of some quality attributes such as the antioxidant capacity (−16%) and the nitrate content in leaves (+48%). Moreover, leaves of successive cuts displayed a significant variation of the profile of bioactive compounds, characterized by an overall decrease of phenylpropanoids and an increase in terpenoids. Our data revealed the impact of CC harvesting strategy in basil, and that this strategy offers the possibility to yield leaves with different metabolomics profiles and quality attributes.